ANALISA KESTABILAN TRANSIEN MENGGUNAKAN METODE TRAJEKTORI KRITIS PADA SISTEM WILAYAH SUMBAR - Ilham Afandi Arista; Arfita Yuana Dewi (Sekolah Tinggi Teknologi Industri Padang, 2022)
This research is to examine the transient stability analysis using the critical trajectory method in the system of the West Sumatra region. Transient stability plays an important role for safety and reliability in the electric power system which aims to estimate the condition of the system when an outage occurs, either in the form of line discharge or generator discharge. This study discusses the stability of transients that occur due to disturbances in the system that affect the generator. When a disturbance occurs, the system will be in a transient state. In this condition, the safety relay will work to open the circuit breaker within a certain time. However, this does not guarantee that the system will return to steady state conditions. This study discusses the stability of transients that occur due to disturbances in the system that affect the generator. When a disturbance occurs, the system will be in a transient state. In this condition, the safety relay will work to open the circuit breaker within a certain time. However, this does not guarantee that the system will return to steady state conditions. After the disturbance the system will return to stability with a tcb open time of 0.300 second, while when the release of channel 10 between the Pauh Limo-Simpang Haru buses occurs with a tcb open time of 0.250 seconds, the critical clearing time value is 1.143 seconds, then the critical path that occurs in the simulation results the time of the loose line between the Pauh Limo-Simpang Haru bus is 1.143-1.144 second.